Better Business Regulation in a Risk Society - Alemanno, Alberto; den Butter, Frank; Nijsen, André; Torriti, Jacopo; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The premise of this volume is that business regulations are expected to grow in the near future as a consequence of the emergence of a “(world) risk society.” Risks related to terrorism, climate change, and financial crises, for example, will penetrate all conditions of life. Increasingly, the decisions and actions of some bring about risks for many in this era of globalization. Controlling these risks implies managing the world through high-quality regulation, with a particular emphasis on businesses and financial institutions. Central to this approach is the argument that a major, if not the primary, aim of regulation is to internalize externalities, or in a broader context, to repair market failure. Such repair can only be accomplished when the costs are smaller than the welfare gains. Featuring contributions from researchers and policy analysts from the fields of economics, management, law, sociology, political science, and environmental policy, this book focuses on three major topics: Social risks and business regulation Preconditions for better business regulation Theoretical issues related to better business regulation Collectively, the authors demonstrate that the easier it is for regulated businesses to comply at the lowest costs possible—without jeopardizing the related public goals—the greater the degree of compliance.  When successful, the net result is a balance of individual and collective net benefits, and by further implication, sustainable business practice and economic growth.
Keywords: Economic policy; Public finance; Economic Policy; Public Economics